2022
DOI: 10.1051/0004-6361/202142873
|View full text |Cite
|
Sign up to set email alerts
|

The magnetic drivers of campfires seen by the Polarimetric and Helioseismic Imager (PHI) on Solar Orbiter

Abstract: Context. The Extreme Ultraviolet Imager (EUI) on board the Solar Orbiter (SO) spacecraft observed small extreme ultraviolet (EUV) bursts, termed campfires, that have been proposed to be brightenings near the apexes of low-lying loops in the quiet-Sun atmosphere. The underlying magnetic processes driving these campfires are not understood. Aims. During the cruise phase of SO and at a distance of 0.523 AU from the Sun, the Polarimetric and Helioseismic Imager on Solar Orbiter (SO/PHI) observed a quiet-Sun region… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Later Kahil et al (2022) also examined the line-of-sight photospheric magnetic field evolution of campfires using Solar Orbiter's PHI data and found similar results to Panesar et al (2021), in that majority of campfires are triggered by magnetic flux cancelation. Some of the campfires show similarities with coronal jets (e.g., Panesar et al 2016bPanesar et al , 2018aHou et al 2021;Panesar et al 2021).…”
Section: Introductionmentioning
confidence: 74%
“…Later Kahil et al (2022) also examined the line-of-sight photospheric magnetic field evolution of campfires using Solar Orbiter's PHI data and found similar results to Panesar et al (2021), in that majority of campfires are triggered by magnetic flux cancelation. Some of the campfires show similarities with coronal jets (e.g., Panesar et al 2016bPanesar et al , 2018aHou et al 2021;Panesar et al 2021).…”
Section: Introductionmentioning
confidence: 74%
“…The “X” indicates the location of one of the detected simulated brightenings, which occurs between opposite-polarity magnetic-field patches (indicated with red and blue contours). EUV brightenings are usually observed to occur between opposite magnetic-field polarities (e.g., Zhukov et al., 2021 ; Kahil et al., 2022 ). While it is beyond the scope of the current study to investigate the relationship between individual simulated brightenings and the magnetic-field configuration, this will be considered in the future, when high-resolution SO/PHI observations are available to drive the simulation at the same time and with the same cadence as the EUI observations.…”
Section: Simulationmentioning
confidence: 99%
“…Previous EUI observations have shown that the EUV brightenings are located between 1000 km and 5000 km above the photosphere (Zhukov et al., 2021 ). Most EUV brightenings appear to be located at the neutral line between patches of two opposite magnetic-field polarities (Panesar et al., 2021 ; Kahil et al., 2022 ), indicating the importance of the magnetic field in the formation and evolution of these features.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, flux cancellation in regions of complex mixed polarity has been observed in association with brightenings in the cores of active regions (Chitta et al 2018(Chitta et al , 2020. Also, evidence has been presented that most of the small-scale campfires are formed by magnetic reconnection driven by flux cancellation (Panesar et al 2021), which occurs either between two main footpoints of a bipolar feature or between one of those footpoints and a nearby magnetic fragment of opposite polarity (Kahil et al 2022).…”
Section: Introductionmentioning
confidence: 96%